Not Just CTEPH: A Narrative Review on the Spectrum Approach to Postpulmonary Embolism Conditions - Biondi, Filippo; Alberti, Mattia; Montemaggi, Elisa; D'Alleva, Alberto; Madonna, Rosalinda (Thrombosis and Haemostasis, 2024)
Three mutually exclusive entities can underlie a postpulmonary embolism syndrome (PPES): not obstructed postpulmonary embolism syndrome (post-PE dyspnea), chronic thromboembolic pulmonary disease (CTEPD), and chronic thromboembolic pulmonary hypertension (CTEPH). Cardiorespiratory impairment in CTEPH and CTEPD underlies respiratory and hemodynamic mechanisms, either at rest or at exercise. Gas exchange is affected by the space effect, the increased blood velocity, and, possibly, intracardiac right to left shunts. As for hemodynamic effects, after a period of compensation, the right ventricle dilates and fails, which results in retrograde and anterograde right heart failure. Little is known on the pathophysiology of post-PE dyspnea, which has been reported in highly comorbid with lung and heart diseases, so that a “two-hit” hypothesis can be put forward: it might be caused by the acute myocardial damage caused by pulmonary embolism in the context of preexisting cardiac and/or respiratory diseases. More than one-third of PE survivors develops PPES, with only a small fraction (3–4%) represented by CTEPH. A value of ≈3% is a plausible estimate for the incidence of CTEPD. Growing evidence supports the role of CTEPD as a hemodynamic phenotype intermediate between post-PE dyspnea and CTEPH, but it still remains to be ascertained whether it constantly underlies exercise-induced pulmonary hypertension and if it is a precursor of CTEPH. Further research is needed to improve the understanding and the management of CTEPD and post-PE dyspnea.
Keywords: venous thromboembolism; chronic thromboembolic pulmonary disease; chronic thromboembolic pulmonary hypertension; exercise-induced pulmonary hypertension